Strategi Pengembangan Desa Wisata Dayeuhkolot Kecamatan Sagalaherang Kabupaten Subang - Rivaldi Noval Gumilar; Saraswati (UNISBA Press, 2023)
Abstract. The development of tourism in Indonesia continues to increase, this is used by the government in improving the economy of the community and the country. The existence of various potentials owned by each region is the main capital in the development of the tourism sector, one of which supports the creation of a tourist village. A tourist village is an area that offers various types of existing tourism potential, such as natural attractions, culture, and local community creativity with the support of attractions, amenities, accessibility and other facilities to attract tourists to visit the tourist village. Dayeuhkolot Village itself has the goal of becoming a tourist village with various types of potential to be utilized as tourist attractions. Creating a tourist village requires a development strategy in utilizing tourism potential as the main component in a tourist village. This research approach uses a mix method approach or a combination of qualitative and quantitative methods. The types of data used are primary and secondary data obtained through various methods such as interviews, questionnaires, observation, and related literature studies. In addition, this study focuses on management in tourist villages with the support of local community participation in creating good and developing tourist villages. Therefore, it is necessary to have a development strategy as a plan in an effort to realize and market tourist villages so that they can achieve the goal of improving quality in the economic, tourism, and also for the welfare of the surrounding community. Abstrak. Perkembangan pariwisata di Indonesia terus meningkat, hal tersebut dimanfaatkan pemerintah dalam meningkatkan perekonomian masyarakat dan negara. Adanya berbagai potensi yang dimiliki tiap daerah menjadi modal utama dalam pengembangan sektor pariwisata, salah satunya mendukung terciptanya suatu desa wisata. Desa wisata merupakan suatu kawasan yang didalamnya menawarkan berbagai jenis potensi wisata yang ada, seperti atraksi alam, budaya, dan kreativitas masyarakat lokal dengan adanya dukungan atraksi, amenitas, aksesibilitas dan fasilitas lainnya untuk menarik wisatawan berkunjung ke desa wisata tersebut. Desa Dayeuhkolot sendiri memiliki tujuan menjadi desa wisata dengan berbagai jenis potensi yang dimiliki untuk dapat dimanfaatkan menjadi atraksi wisata. Menciptakan suatu desa wisata perlu adanya strategi pengembangan dalam memanfaatkan potensi wisata sebagai komponen utama yang ada dalam suatu desa wisata. Pendekatan penelitian ini menggunakan metode pendekatan mix method atau gabungan dari metode kualitatif dan kuantitatif. Jenis data yang digunakan merupakan data primer dan sekunder yang diperoleh melalui berbagai cara seperti wawancara, kuesioner, observasi, dan studi litelatur yang berkaitan. Selain itu, dalam penelitian ini memfokuskan pada pengelolaan di desa wisata dengan adanya dukungan partisipasi masyarakat lokal dalam menciptakan desa wisata yang baik dan berkembang. Maka dari itu, perlu adanya strategi pengembangan sebagai rencana dalam upaya merealisasikan serta memasarkan desa wisata agar dapat mencapai tujuan untuk meningkatkan kualitas di sektor perekonomian, pariwisata, dan juga bagi kesejahteraan masyarakat sekitar. The development of tourism in Indonesia continues to increase, this is used by the government in improving the economy of the community and the country. The existence of various potentials owned by each region is the main capital in the development of the tourism sector, one of which supports the creation of a tourist village. A tourist village is an area that offers various types of existing tourism potential, such as natural attractions, culture, and local community creativity with the support of attractions, amenities, accessibility and other facilities to attract tourists to visit the tourist village. Dayeuhkolot Village itself has the goal of becoming a tourist village with various types of potential to be utilized as tourist attractions. Creating a tourist village requires a development strategy in utilizing tourism potential as the main component in a tourist village. This research approach uses a mix method approach or a combination of qualitative and quantitative methods. The types of data used are primary and secondary data obtained through various methods such as interviews, questionnaires, observation, and related literature studies. In addition, this study focuses on management in tourist villages with the support of local community participation in creating good and developing tourist villages. Therefore, it is necessary to have a development strategy as a plan in an effort to realize and market tourist villages so that they can achieve the goal of improving quality in the economic, tourism, and also for the welfare of the surrounding community.